2011
DOI: 10.1073/pnas.1102140108
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain protein Brd3 associates with acetylated GATA1 to promote its chromatin occupancy at erythroid target genes

Abstract: Acetylation of histones triggers association with bromodomaincontaining proteins that regulate diverse chromatin-related processes. Although acetylation of transcription factors has been appreciated for some time, the mechanistic consequences are less well understood. The hematopoietic transcription factor GATA1 is acetylated at conserved lysines that are required for its stable association with chromatin. We show that the BET family protein Brd3 binds via its first bromodomain (BD1) to GATA1 in an acetylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
211
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(220 citation statements)
references
References 62 publications
(103 reference statements)
6
211
0
1
Order By: Relevance
“…It is therefore likely that each BET bromodomain has a distinct function although the combined effect seems to be conferring a regulatory output in gene transcription. We observed in this study that targeting the BD2 had only a modest effect on transcription, an observation supported by previous studies of BRD3 that showed that its recruitment to acetylated sites on GATA1 is mediated by BD1 (40). Notably, deletion of the first bromodomain in BRDT in mice is sufficient to confer sterility by blocking BRDT-dependent sperm maturation (39).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is therefore likely that each BET bromodomain has a distinct function although the combined effect seems to be conferring a regulatory output in gene transcription. We observed in this study that targeting the BD2 had only a modest effect on transcription, an observation supported by previous studies of BRD3 that showed that its recruitment to acetylated sites on GATA1 is mediated by BD1 (40). Notably, deletion of the first bromodomain in BRDT in mice is sufficient to confer sterility by blocking BRDT-dependent sperm maturation (39).…”
Section: Discussionsupporting
confidence: 72%
“…The cell type-specific roles have been highlighted by recent reports on BRDT-dependent transcription programs that regulate spermatogenesis (37-39) and BRD3-dependent recruitment of GATA1 in hematopoietic cells regulating maturation of erythroid, megakaryocyte, and mast cell lineages (23,40), as well as BRD2-dependent roles regulating differentiation of adipose tissue (25) and neurons (41). Application of BET inhibitors outside the area of oncology, given the pleiotropic nature of BET transcriptional regulation, strongly suggests a requirement for more selective targeting with respect to isoform and/or domains, to avoid adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…BRD3 has been reported to directly interact with acetylated lysine residues of the transcription factor GATA1, which regulates the expression of all erythroid and megakaryocyte-specific genes [60]. Pull-down of extracts from GATA1-null erythroblasts (G1E cells) expressing normal or mutant forms of HA-tagged BRD3 using acetylated GATA1 peptides shows that lack of BDI interferes with the binding of BRD3 to acetylated peptides, suggesting that recruitment of BRD3 to GATA1-associated Interactions between their bromodomains (BD) and the acetylated lysine (Ac) in histones facilitate the passage of RNA Pol II to elongate nascent transcripts through hyperacetylated nucleosomes.…”
Section: Brd2 and Brd3 Specifically Recognize Acetylated Histones Thrmentioning
confidence: 99%
“…For example, BRD4, a member of the bromo and extra terminal (BET) subfamily of bromodomain-containing proteins, interacts with the acetylated RelA subunit of NF-κB to promote transcriptional activation of inflammatory genes (7). BRD3 has been shown to interact with the acetylated transcription factor GATA1, recruiting this transcription factor to both active and repressed target genes in a histone acetylation-independent fashion (8). Accordingly, there much interest in generating inhibitors to block the interaction between bromodomains and their acetylated binding partners and thus to reverse changes in gene expression in human disease states.…”
mentioning
confidence: 99%